Prognostic value of SARS‐CoV‐2 on patients undergoing cardiac surgery. Issue 1 (30th October 2021) - Bonalumi, Giorgia; Pilozzi Casado, Alberto; Barbone, Alessandro; Garatti, Andrea; Colli, Andrea; Giambuzzi, Ilaria; Torracca, Lucia; Ravenni, Giacomo; Folesani, Gianluca; Murara, Giacomo; Pantaleo, Antonio; Picichè, Marco; et al.
Abstract: Objective: To analyze Italian Cardiac Surgery experience during the pandemic of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) identifying risk factors for overall mortality according to coronavirus disease 2019 (COVID‐19) status. Methods: From February 20 to May 31, 2020, 1354 consecutive adult patients underwent cardiac surgery at 22 Italian Centers; 589 (43.5%), patients came from the red zone. Based on COVID‐19 status, 1306 (96.5%) were negative to SARS‐CoV‐2 (COVID‐N), and 48 (3.5%) were positive to SARS‐CoV‐2 (COVID‐P); among the COVID‐P 11 (22.9%) and 37 (77.1%) become positive, before and after surgery, respectively. Surgical procedures were as follows: 396 (29.2%) isolated coronary artery bypass grafting (CABG), 714 (52.7%) isolated non‐CABG procedures, 207 (15.3%) two associate procedures, and three or more procedures in 37 (2.7%). Heart failure was significantly predominant in group COVID‐N (10.4% vs. 2.5%, p  = .01). Results: Overall in‐hospital mortality was 1.6% (22 cases), being significantly higher in COVID‐P group (10 cases, 20.8% vs. 12, 0.9%, p  < .001). Multivariable analysis identified COVID‐P condition as a predictor of in‐hospital mortality together with emergency status. In the COVID‐P subgroup, the multivariable analysis identified increasing age and low oxygen saturation at admission as risk factors for in‐hospital mortality. Conclusion: As expected, SARS‐CoV‐2 infection, either before or soon after cardiac surgery significantly increases in‐hospital mortality. Moreover, among COVID‐19‐positive patients, older age and poor oxygenation upon admission seem to be associated with worse outcomes.